Does livestock help in compensating land inequalities in rural India: Evidences from agricultural census? - Kaur, Manpreet; Singla, Naresh (Indian Journal of Dairy Science, 2022)
Using data of various rounds of Agricultural Census, the study has revealed that rural inequalities are largely attributed to disparities in ownership of land leading to unequal distribution of income. Land inequalities during various rounds among various farmer categories have remained almost constant with minor fluctuations, whereas inequalities in ownership of various livestock such as cattle, buffalo, horse and pony have reduced drastically. The extent of land inequalties is also found to be much larger than livestock inequalties. Small size of operated area among marginal and small cultivators is compensated by ownership of cattle and buffalo, which helps to mitigate inequalities caused by land. The study concludes that government policies should be targeted at strengthening sustained development of livestock activities, which can go a long way in mitigating land inequalities and removing agrarian distress.